Loss of Medicaid Insurance After Successful Bariatric Surgery: An Unintended Outcome - Mehaffey, J. Hunter (Surg Endosc, 2017)
BACKGROUND: Bariatric surgery leads to dramatic weight loss and improved overall health, which may affect insurance status for certain patients. Traditional Medicaid provides coverage for children, pregnant women, and disabled adults, while expanded Medicaid provides insurance coverage to all adults with incomes up to 138% of the federal poverty level. We hypothesized that successful bariatric surgery would lead to improved health status but an unintended loss of Medicaid coverage. METHODS: All patients who underwent bariatric surgery at a single institution in a non-expansion state from 1985 through 2015 were identified using a prospectively collected database. Univariate and multivariate analyses were used to identify differences in patients who lost Medicaid coverage after bariatric surgery. RESULTS: Over the 30-year study period, 3,487 patients underwent bariatric surgery, with 373 (10.7%) having Medicaid coverage at the time of surgery. This cohort of patients had a median age of 37 years and preoperative Body Mass Index (BMI) of 54 kg/m(2). At one-year follow-up, 155 (41.6%) of patients lost Medicaid coverage, of which 76 (49.0%) had no coverage. The preoperative prevalence of diabetes (32.3 vs. 44.0%, p=0.02), age (36 vs. 38 years, p=0.01) and BMI (53 vs. 55 kg/m(2), p=0.04) were significantly lower in patients who no longer qualified for Medicaid after bariatric surgery. Multivariate regression demonstrated that For every 10 point increase in BMI (OR 0.755, p=0.01), a patient was 25% less likely to lose their coverage at one year. CONCLUSIONS: Successful surgery in a state not expanding Medicaid resulted in over 40% of patients losing Medicaid coverage postoperatively, with half of those patients returning for follow-up with no insurance coverage at all. This barrier to care has major implications in patients undergoing bariatric surgery, which requires life long follow-up and nutrition screening.